T-SCAN: AN ADVANCED SYSTEM FOR OCCLUSION ANALYSIS IN DENTISTRY (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Digital technologies are increasingly being integrated into modern dental diagnostics, particularly in the assessment of occlusion. One of the most advanced tools in this field is the T-Scan system, which has largely replaced traditional articulating paper by providing precise and dynamic occlusal analysis.